An Expert-driven Ontology-based Approach to the Collaborative Acquisition of Information - Sanchez, Alejandro (2017)
This article presents design decisions for an ontologybased framework supporting an expert-driven approach to the collaborative acquisition, integration and analysis of information. It describes a three-tier organization in which components facilitate establishing an information system to assist domain experts in addressing multi-causal dynamic situations where heterogeneous information sources must be integrated and the interaction of a variety of actors must be supported in large geographical areas with possibly low or intermittent connectivity levels. The approach and envisioned framework are illustrated with a case-study in the design of bikeways in urban zones.